EVALUATION OF ACUTE AND SUB-ACUTE TOXICITY OF METHANOLIC LEAF EXTRACT OF BAMBUSA VULGARIS ON MALE WISTAR RATS - SARKAR, SUSMITA; ROY CHOWDHURY, PANISREE; CHOUDHURI, DIPAYAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The study aims to evaluate the potential toxicity of methanolic extract of leaves of Bambusa vulgaris in male Wistar rats. Methods: The methanolic extract was prepared for acute and sub-acute toxicity to determine the lethal dose. During the acute toxicity study, male rats were orally administered with leaf extracts at single doses of 100, 500,800, and 2000 mg/kg according to OECD Guidelines 425 for 14 days. Sub-acute toxicity dose at 200, 400, and 800 mg/kg was studied by daily dosing on male rats for 30 days. Results: The acute toxicity study revealed no lethal effects and behavioral signs of toxicity at the tested doses indicating that LD50 is <2000 mg/kg. In a sub-acute study, non-significant changes in the body weight (p<0.05), body weight gain percentage (p<0.05) food intake (p<0.05), and relative organ weight percentage (p<0.05), and hematological parameters (p<0.05) of the rats were observed. A significant (p<0.05) increase in ALT level was observed dose at 800 mg/kg. Histopathological analysis showed mild cell distortion in the liver and kidney in male rats treated at 800 mg/kg of extract. Conclusion: Our study suggests that oral administration of methanolic leaf extract Bambusa vulgais is safe. However, a dose of 800 mg/kg may be toxic for the liver and kidney.